2010
DOI: 10.1021/ja101860r
|View full text |Cite
|
Sign up to set email alerts
|

The Polar Phase of NaNbO3: A Combined Study by Powder Diffraction, Solid-State NMR, and First-Principles Calculations

Abstract: A polar phase of NaNbO(3) has been successfully synthesized using sol-gel techniques. Detailed characterization of this phase has been undertaken using high-resolution powder diffraction (X-ray and neutron) and (23)Na multiple-quantum (MQ) MAS NMR, supported by second harmonic generation measurements and density functional theory calculations. Samples of NaNbO(3) were also synthesized using conventional solid-state methods and were observed to routinely comprise of a mixture of two different polymorphs of NaNb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
198
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(207 citation statements)
references
References 46 publications
8
198
0
1
Order By: Relevance
“…In addition, benchmark calculations have been carried out for the high-temperature simple cubic perovskite phase (Pm3m, SG 221, Z � 1). All four phases have been initially set up using experimental data reported by Jiang et al [28] for the Pm3m phase, by Cheon et al [5] for the Pm phase, by Johnston et al [6] for the Pbcm phase, and by Darlington and Megaw [4] for the R3c phase, respectively. For all four phases, we performed a full geometry optimisation for several unit-cell volumes centred around the experimentally reported ones.…”
Section: Crystalline Phases At Room Temperature Andmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, benchmark calculations have been carried out for the high-temperature simple cubic perovskite phase (Pm3m, SG 221, Z � 1). All four phases have been initially set up using experimental data reported by Jiang et al [28] for the Pm3m phase, by Cheon et al [5] for the Pm phase, by Johnston et al [6] for the Pbcm phase, and by Darlington and Megaw [4] for the R3c phase, respectively. For all four phases, we performed a full geometry optimisation for several unit-cell volumes centred around the experimentally reported ones.…”
Section: Crystalline Phases At Room Temperature Andmentioning
confidence: 99%
“…Darlington et al [4] and Cheon et al [5] reported on a possible admixture of a monoclinic phase (Pm) into the room-temperature orthorhombic AFE P phase (Pbcm) based on X-ray diffraction and neutron powder diffraction measurements. ere are also reports about a room-temperature phase transition into a FE phase (P2 1 ma) induced by an applied electric field [6,7], by nanoparticle growth [8] or by growth as a strained thin film [9], respectively. A full list of recent experimental data can be found in [2,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…4 , 5 , 6 Although itself antiferroelectric (orthorhombic, Phase P, space group Pbcm) at ambient temperature, NaNbO 3 becomes ferroelectric (rhombohedral, Phase N, space group R3c, Glazer tilt system 7 a -a -a -) below 173 K. Depending on sample synthesis conditions, a ferroelectric polymorph, Phase Q (orthorhombic, space group P2 1 ma, Glazer tilt system a -b + a -) can co-exist with Phase P at room temperature. 8,9 Moreover, the orthorhombic ferroelectric phase of NaNbO 3 can be made via chemical doping; indeed doping as little as 2% of either potassium or lithium, to form the solid solutions K x Na 1-x NbO 3 or Li x Na 1-x NbO 3 , induces both a change in the octahedral tilt system of Phase P and a polarization to produce Phase Q. 10 The composition-dependent phase diagram of KNN has recently been re-analysed and is now fairly well understood, 11,12 but that of LNN has received much less attention.…”
Section: Introductionmentioning
confidence: 99%
“…NaNbO 3 also exhibits complex polymorphism related from the synthetic route used. A polar polymorph may be synthesised when a sol-gel method is used and the ilmenite polymorph of NaNbO 3 can only be prepared via hydrothermal synthesis [18,19]; by adjusting the hydrothermal reaction conditions, a perovskite polymorph may be obtained [19]. NaNbO 3 also displays crystallite size related polymorphism [20].…”
Section: Introductionmentioning
confidence: 99%